2022
DOI: 10.2147/ijgm.s357427
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Therapy, Survival and Renal Replacement Therapy in Burn Patients: A 10-Year Single-Center Cohort Study

Abstract: Purpose Colistin is still a therapeutic cornerstone against multidrug-resistant gram-negative bacteria (MDRGN), mostly when other antibiotics do not gain adequate activity on these strains. In the present study, we evaluated in a cohort of burn patients the relationship between colistin therapy, survival and requirement of renal replacement therapy (CRRT). Patients and Methods Retrospective study of 133 burn patients treated with iv colistimethate sodium (loading dose 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Despite its potential adverse effects on renal function, colistin continues to play a key role as salvage treatment in burn patients. Mariano et al [21] reported…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its potential adverse effects on renal function, colistin continues to play a key role as salvage treatment in burn patients. Mariano et al [21] reported…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potential adverse effects on renal function, colistin continues to play a key role as salvage treatment in burn patients. Mariano et al [ 21 ] reported that colistin therapy can lead to clinical success without a significant association with severe renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…One study in rats showed that polymyxin=-induced nephrotoxicity was related to the frequency of dosing [28]. A 10-year cohort study found that nephrotoxicity is related to the dose and the number of days of administration [29]. In this study, the drug exposure of MRX-8 was approximately 1.5-fold and 1.3-fold higher than PMB at the dose of 8 mg/kg, while MRX-8 showed lower nephrotoxicity than PMB at the same dose.…”
Section: Discussionmentioning
confidence: 99%
“…Usage of Colistin is frequently associated with Nephrotoxicity and incidence of CRRT during or after completion of the therapeutic course however there are several studies that support the safety of Colistin Therapy. 13 Moreover, combination therapy e.g., Carbapenem with Colistin or Amikacin is routinely used in clinical practice to broaden the antimicrobial spectrum and reduce the risk of initial inappropriate therapy, although its potential for antimicrobial synergy and delaying or preventing antimicrobial resistance remains a subject of constant scrutiny and progressive research. 14 In our clinical setting, the problem of MRD and XDR is a nuisance in treatment of major burns which overlaps with overcrowding of patients and extended hospital stay.…”
Section: Discussionmentioning
confidence: 99%